2020
DOI: 10.1101/2020.03.29.20047159
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection in health care workers: a retrospective analysis and model study

Abstract: BackgroundThere had been a preliminary occurrence of human-to-human transmissions between healthcare workers (HCWs), but risk factors in the susceptibility for COVID-19, and infection patterns among HCWs have largely remained unknown. MethodsRetrospective data collection on demographics, lifestyles, contact status with infected subjects for 118 HCWs (include 12 COVID-19 HCWs) from a single-center. Sleep

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 14 publications
1
52
4
Order By: Relevance
“…This study revealed chances of getting infected were more among patients in ICU than inpatients, but the difference was not statistically signi cant. In contrast, Wuhan's study showed that physicians working in ICU had two times more chances of getting infected than the general wards [23]. This difference could be due to the lower number of respondents had been working in ICU in our study.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…This study revealed chances of getting infected were more among patients in ICU than inpatients, but the difference was not statistically signi cant. In contrast, Wuhan's study showed that physicians working in ICU had two times more chances of getting infected than the general wards [23]. This difference could be due to the lower number of respondents had been working in ICU in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…From this nding, it seems that the physicians in Bangladesh were affected at a relatively younger age. At Wuhan, relatively older-aged physicians were affected with COVID-19, and the age difference between infected and uninfected physicians was signi cant [23]. However, in our study, no statistically signi cant difference was found regarding the age among these two groups.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…A study conducted on physicians in the USA showed that the median age of physicians being affected was 42 years [7]. Another study conducted in Wuhan, China, revealed that the mean age of the affected physicians was 37 years [23]. From this finding, it seems that the physicians in Bangladesh were affected at a relatively younger age.…”
Section: Discussionmentioning
confidence: 99%